Diklat Kolaboratif Untuk Akselerasi Peningkatan Kompetensi Guru Madrasah - Nanang Rosidi (Biro Perencanaan Kementerian Agama, 2022)
The results of the Teacher Competency Assessment (AKG) in 2020 show that the competence of madrasa teachers is still relatively low. This condition not only has an impact on the quality of madrasa education, but also on the achievement of national education performance. The low competence of madrasa teachers is due to the limited quota of training to increase the competence of madrasa teachers. This study aims to find a strategy for accelerating madrasa teacher competency improvement. This study uses a qualitative approach with descriptive analytical research methods. Data collection techniques were carried out through literature reviews originating from books, journals, applicable laws and regulations, as well as through interviews. The results of this study indicate that the acceleration of madrasa teacher competency improvement can be done through a collaborative training scheme, in which the implementation of Teacher Professional Education (PPG) is not only carried out by the Direktorat Jenderal Pendidikan Islam through LPTK, but also by all competent institutions, both public and private. The competency test remains the authority of the Direktorat Jenderal Pendidikan Islam. In addition, it is necessary to affirm the PKB Guru program and training programs organized by Pusdiklat Tenaga Teknis and BDK as programs that are equivalent to PPG. Keywords: AKG; PPG; LPTK; Madrasah Teachers